(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
Amalgamation of compression and security is indispensable in the field of multimedia applications. A novel approach to enhance security with compression is discussed in this Â research paper. In secure arithmetic coder (SAC), security is provided by input and output permutation methods and compression is done by interval splitting arithmetic coding. Permutation in SAC is susceptible to attacks. Encryption issues associated with SAC is dealt in this research method. The aim of this proposed method is to encrypt the data first by Table Substitution Box (T-box) and then to compress by Interval Splitting Arithmetic Coder (ISAC). This method incorporates dynamic T-box in order to provide better security. T-box is a method, constituting elements based on the random output of Pseudo Random Generator (PRNG), which gets the input from Secure Hash Algorithm-256 (SHA-256) message digest. The current scheme is created, based on the key, which is known to the encoder and decoder. Further, T-boxes are created by using the previous message digest as a key. Â Existing interval splitting arithmetic coding of SAC is applied for compression of text data. Interval splitting finds a relative position to split the intervals and this in turn brings out compression. The result divulges that permutation replaced by T-box method provides enhanced security than SAC. Data is not revealed when permutation is replaced by T-box method. Security exploration reveals that the data remains secure to cipher text attacks, known plain text attacks and chosen plain text attacks. This approach results in increased security to Interval ISAC. Additionally the compression ratioÂ is compared by transferring the outcome of T-boxÂ to traditionalÂ arithmetic coding. The comparison proved that there is a minor reduction in compression ratio in ISAC than arithmetic coding. However the security provided by ISAC overcomes the issues of compression ratio inÂ arithmetic coding. Â